Improving or worsening? : the development and evaluation of a VR-based psychotherapy to bullying victims and perpetrators in school adolescents - Mulyono, Sigit; Setiawan, Agus; Sari, Indah Permata; Rachmawati, Utami; Yulianti, Eka Putri; Putri, Tissa Aulia; Siahaan, Eva Winda Sarma; Shabrina, Citra Hafilah; Runesi, Odis; Suhaiba, Suhaiba (Universitas Airlangga, 2025)
Introduction: This study evaluated the effectiveness of a Virtual Reality (VR)-based emotional regulation intervention in addressing bullying among school adolescents, focusing on changes in self-perceived roles as victims or bullies and associated difficulties. Methods: This study used a quasi-experimental design, with 98 junior high school students assigned to either a four-session VR intervention (n=33) or a no-treatment control group (n=65). The intervention consisted of four 15-minute psychotherapy sessions using the PeriXa Batin VR module. Data were collected using the Strengths and Difficulties Questionnaire and System Usability Scale (SUS). Statistical analyses included the Mann-Whitney U test, a General Linear Model (GLM), and thematic analysis. Results: The intervention was associated with a significant reduction in self-perceived bullying behaviors (p < 0.001), particularly among males. However, it also led to an increase in self-reported difficulty scores (p < 0.005). The VR module was received positively, with high usability ratings, although some participants reported minor technical issues and temporary discomfort, such as dizziness. The VR intervention effectively fostered self-awareness, which may explain both the reduction in bullying and the concurrent increase in emotional distress as victims confronted their experiences. The limitations include short intervention duration, small sample size, and reliance on self-reported data. Conclusions: While VR is a promising tool, schools should implement it alongside support systems, such as counseling, to help students manage the challenges of increased self-awareness. Future research should focus on the long-term effects and integration of such technologies into comprehensive school wellness programs.